Excess mortality Measuring the direct and indirect impact of COVID-19 - Morgan, David (OECD Health Working Papers, 2020)
Assessing the direct and indirect health impact of the COVID 19 pandemic is central in managing public health and other policy measures while learning to co-exist with the virus. Many countries are publishing statistics on COVID 19 related mortality. While the frequent and timely publication of such figures provides insights into the ongoing trends in a given country, differences in coding and reporting practices pose challenges for international comparisons. Looking at the number of total deaths can help to overcome some of these differences in national practices whilst also providing a better view of the overall impact of COVID 19, by taking into account not just the possible underreporting of COVID 19 deaths but also indirect mortality caused, for example, by health systems not being able to cope with other conditions - acute and chronic